The Influence Of Leadership, Supervision, Assistance, Penalties And Benefits On Employee Discipline At The Office Of The Ministry Of Religion, Muara Enim District - Eki Martina; Abdul Hamid; NIsma Aprini (Penerbit Jurnal Indonesia, 2023)
This research aims to analyze and determine the influence of leadership, supervision, firmness, punitive sanctions, and allowances on employee discipline at the Office of the Ministry of Religion of Muara Enim Regency, either partially or simultaneously. This study used a quantitative research method with respondents namely employees of the office of the Ministry of Religion of Muara Enim Regency, totaling 44 employees and Head of the Office of Religious Affairs in Muara Enim Regency, totaling 20 people. Tests in this study used multiple linear regression analysis with the tools of the SPSS (Special Package and Service Solution) version 26 program. The results of the research show that leadership, supervision, firmness, punitive sanctions, and allowances affect employee discipline at the Office of the Ministry of Religion of Muara Enim Regency both partially and simultaneously. In this study, leadership has the highest influence with a regression coefficient value of 0.257, while the lowest is Punishment with a regression coefficient value of 0.081.